Prospective of socio-educational research in Peru - Ríos Burga, Jaime (2018)
This article seeks to locate prospectively in the global systemic framework of changing societies and situations central issues of socio-educational research in Peru today. Highlight some of the main lines of research and new socio- political scientific challenges.